Syntactische atlas van de Nederlandse dialecten Deel II - Barbiers, Sjef (SAND, 2008)
The Syntactic Atlas of the Dutch Dialects (SAND) provides a detailed overview of the surprisingly rich syntactic variation found in 267 dialects of Dutch at the beginning of the 21st century. More than 200 full color maps show the geographic distributiebon of over 100 syntactic variables. Many of these variables involve phenomena that are absent form the standard language and thus of great descriptive and theoretical importante. A state-of-the art linguistic description and commentary accompanies each map, taking into account the results of modern syntactic research as well as historical developments. Volume I (2005) shows the variation in complementisers and complementiser agreement, subject pronouns, subject doubling and subject clitisation after yes/ no, reflexives and reciprocals, relative clauses, question-word doubling and topicalisation. Volume II shows the variation in two- and three verb clusters, interruption of the verb clusters, extraposition and te 'to' in the verbal clusters, auxiliary selection, do-insertion, and negation and quantification.